A study on the comparison of minimally invasive surfactant therapy with insure technique of surfactant therapy in preterm babies with respiratory distress in a tertiary care hospital – A prospective cohort study - Akhila, Andra; Ghoshal, Bhaswati; Mahapatra, Nepal Chandra (Indian Journal of Child Health, 2021)
Background: Respiratory distress syndrome (RDS) is a common problem in preterm babies due to surfactant deficiency. Initially, babies were given surfactant therapy by intubation, surfactant administration, and extubation (INSURE) method. Minimally invasive surfactant therapy (MIST) is a novel method of surfactant administration without intubation to spontaneously breathing preterm babies with RDS without the removal of continuous positive airway pressure (CPAP). Aim: This study aims to compare the surfactant therapy in preterm babies with RDS through MIST and INSURE technique. Methods: This prospective, observational cohort study was conducted in the neonatology unit of Calcutta National Medical College and Hospital. A total of 212 preterm babies of